Niobium‐Based Oxides Toward Advanced Electrochemical Energy Storage: Recent Advances and Challenges. Issue 32 (14th February 2019) - Deng, Qinglin; Fu, Yanpeng; Zhu, Changbao; Yu, Yan
Abstract: Niobium‐based oxides including Nb2 O5, TiNb x O2+2.5 x compounds, M–Nb–O (M = Cr, Ga, Fe, Zr, Mg, etc.) family, etc., as the unique structural merit (e.g., quasi‐2D network for Li‐ion incorporation, open and stable Wadsley– Roth shear crystal structure), are of great interest for applications in energy storage systems such as Li/Na‐ion batteries and hybrid supercapacitors. Most of these Nb‐based oxides show high operating voltage (>1.0 V vs Li + /Li) that can suppress the formation of solid electrolyte interface film and lithium dendrites, ensuring the safety of working batteries. Outstanding rate capability is impressive, which can be derived from their fast intercalation pseudocapacitive kinetics. However, the intrinsic poor electrical conductivity hinders their energy storage applications. Various strategies including structure optimization, surface engineering, and carbon modification are effectively used to overcome the issues. This review provides a comprehensive summary on the latest progress of Nb‐based oxides for advanced electrochemical energy storage applications. Major impactful work is outlined, promising research directions, and various performance‐optimizing strategies, as well as the energy storage mechanisms investigated by combining theoretical calculations and various electrochemical characterization techniques. In addition, challenges and perspectives for future research and commercial applications are also presented. Abstract : Niobium‐based oxides including Nb2 O5, TiNb x O2+2.5x compounds, M–Nb–O family, etc., as the unique structural merit and intercalation pseudocapacitive kinetics, are of great interest for applications in energy storage systems such as Li/Na‐ion batteries and hybrid supercapacitors to gather the scattered energies.